The Effect Of Butterfly Hug Therapy On Reducing Anxiety Level Of Laparotomy Pre-Operation Patients : Pengaruh Terapi Butterfly Hug Terhadap Penurunan Tingkat Kecemasan Pasien Pre-Operasi Laparotomi - Chairani, Reni; Nadidah Faras Dita Putri, Nada; Mumpuni, Mumpuni (Essential English Grammar, 2024)
Usually patients will feel psychological and physiological stress before surgery which can increased heart rate, blood pressure, and breathing. One of the operations causes excessive anxiety is laparotomy. From the National Social Security Council, (2022) in 2020 laparotomy surgery participants in Indonesia was 12,537 and in 2021 it became 13,131. Anxiety in pre-laparotomy patients caused by psychological readiness for surgery that has not yet occurred. Butterfly hug developed by therapists Luciana and Janero. This therapy provides a comfort, reduces physical pain and increases a sense of calm through the comfort of a hug. This study aims to analyze the effect of butterfly hug on reducing pre-laparotomy surgery anxiety. This research method is a Quasy Experiment Pre-test – Post-test with control group. The dependent variable is pre-laparotomy patient anxiety and butterfly hug as an independent variable. The study population was pre-operative patients who experienced anxiety with a sample of 41 respondents. This research instrument uses a modified butterfly hug SOP and a zung self-anxiety scale questionnaire to assess anxiety. Data analysis uses Wilcoxon test. Statistically, the results obtained a p-value of 0.000 <0.05 which indicates that an effect of butterfly hug therapy on reducing the level of anxiety in pre-laparotomy patients